Calorie Restriction Curbs Proinflammation That Accompanies Arterial Aging, Preserving a Youthful Phenotype. Issue 18 (18th September 2018) - Wang, Mingyi; Zhang, Li; Zhu, Wanqu; Zhang, Jing; Kim, Soo Hyuk; Wang, Yushi; Ni, Leng; Telljohann, Richard; Monticone, Robert E.; McGraw, Kimberly; Liu, Lijuan; de Cabo, Rafael; et al.
Abstract : Background: Aging exponentially increases the incidence of morbidity and mortality of quintessential cardiovascular disease mainly due to arterial proinflammatory shifts at the molecular, cellular, and tissue levels within the arterial wall. Calorie restriction (CR) in rats improves arterial function and extends both health span and life span. How CR affects the proinflammatory landscape of molecular, cellular, and tissue phenotypic shifts within the arterial wall in rats, however, remains to be elucidated. Methods and Results: Aortae were harvested from young (6‐month‐old) and old (24‐month‐old) Fischer 344 rats, fed ad libitum and a second group maintained on a 40% CR beginning at 1 month of age. Histopathologic and morphometric analysis of the arterial wall demonstrated that CR markedly reduced age‐associated intimal medial thickening, collagen deposition, and elastin fractionation/degradation within the arterial walls. Immunostaining/blotting showed that CR effectively prevented an age‐associated increase in the density of platelet‐derived growth factor, matrix metalloproteinase type II activity, and transforming growth factor beta 1 and its downstream signaling molecules, phospho‐mothers against decapentaplegic homolog‐2/3 (p‐SMAD‐2/3) in the arterial wall. In early passage cultured vascular smooth muscle cells isolated from AL and CR rat aortae, CR alleviated the age‐associated vascular smooth muscle cell phenotypic shifts, profibrogenic signaling, and migration/proliferation in response to platelet‐derived growth factor. Conclusions: CR reduces matrix and cellular proinflammation associated with aging that occurs within the aortic wall and that are attributable to platelet‐derived growth factor signaling. Thus, CR reduces the platelet‐derived growth factor–associated signaling cascade, contributing to the postponement of biological aging and preservation of a more youthful aortic wall phenotype.